Contingency in Marx: The Problem of «Collisions» - Antonio Cerquitelli (Scienza & Politica)
Through the lexicon of collisions, Marx recognises the necessity of the contingency, attested by the political experimentation that emerges on the level of empiricism. Collisions, according to the model of a totality «articulated in dominance», perturb the life of the whole, making the order established by property constitutively precarious.